2006
DOI: 10.1373/clinchem.2006.070912
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Brain Biomarkers

Abstract: Background:The diagnosis of diseases leading to brain injury, such as stroke, Alzheimer disease, and Parkinson disease, can often be problematic. In this study, we pursued the discovery of biomarkers that might be specific and sensitive to brain injury. Methods: We performed gene array analyses on a mouse model to look for biomarkers that are both preferentially and abundantly produced in the brain. Via bioinformatics databases, we identified the human homologs of genes that appeared abundant in brain but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 41 publications
2
96
0
3
Order By: Relevance
“…These findings indicate that tau protein concentrations in CSF probably reflect axonal damage. Visinin-like protein-1 also has recently been identified as a promising biomarker for brain injury (32 ). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that tau protein concentrations in CSF probably reflect axonal damage. Visinin-like protein-1 also has recently been identified as a promising biomarker for brain injury (32 ). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two rabbits (9472 and 9473) were each immunized with an equal concentration mixture of KLH-P-4840 (G 53 GNKKRRQINEDE 65 ) and KLH-P-4841 (G 8 GGSPKGDVDPFYY 21 ) at Harlan Bioproducts for Sciences (Madison, WI). Individual rabbit antiserum was affinity-purified over a SulfoLink P-4840 column with the non-bound flow-through applied to a SulfoLink P-4841 column.…”
Section: Antibody Production and Characterizationmentioning
confidence: 99%
“…Antibody concentration was determined by UV scanning from 240 to 320 nm, using A 280 ¼ 1.4 ml/(mg Á cm) and then stored at 4 1C. The procedure for western blots has been described, 21 and the alkaline phosphatase substrate for western blots 5-bromo,4-chloro,3-indoylphosphate/nitrobluetetrazolium was obtained from Kirkegaard and Perry (Gaithersburg, MD).…”
Section: Antibody Production and Characterizationmentioning
confidence: 99%
“…Perhaps because of the daunting complexity of plasma profiling, as well as the recent successful application of transcript profiling to the field of cancer biomarkers (6 ), Laterza et al (1 ) opted for the latter, more mature technology for the identification of novel biomarkers of brain injury. Using transcript profiling of isolated organ preparations, Laterza et al identified mRNAs that were highly enriched in the brain.…”
Section: Biomarker Discovery and Validationmentioning
confidence: 99%